Komunikasi Artifaktual Status Instagram “Ning” Pondok Pesantren - Jannah, Anifatul (Jurnal Komunikasi Islam, 2018)
The development of social media apparently also influenced social communication amongst the pesantren community, including the daughter of the Kiai, called as "ning". This article discusses artifactual communication on Instagram status which was uploaded by "Ning" of Islamic boarding school (Pondok pesantren). Using a text analysis approach, the results of this study concluded that uploaded images on Instagram conducted periodically by "Ning" of Pondok pesantren was a form of a non-verbal message pattern that could be interpreted as artifactual communication, which reflected the established and high socio-economic class "Ning" as the Kiai’s daughter. In addition, the respect given to Kiai’s daughter on social media was similar to what occurred in real life. In this sense, the polite attitude which was found in the cyber community was the reflection that occurred in the offline reality in pesantren.